TROCA OU PERMUTA (REMUNOM, 2025)
This article examines the institution of exchange and barter in the context of Brazilian civil law, addressing legal and practical aspects related to these types of contracts. Initially, the importance of these institutions in the Brazilian legal system is contextualized, highlighting their historical significance and contemporary applicability. Through a detailed analysis of relevant legal provisions of the Brazilian Civil Code, the study explores the essential elements that characterize exchange and barter, such as consent of the parties, lawful object, and equivalence of value. Additionally, the differences between these two types of contracts are discussed, emphasizing their peculiarities and legal consequences. Subsequently, practical cases and jurisprudential analyses illustrating the application of principles related to exchange and barter in Brazilian civil law are examined. Examples of situations involving judicial disputes concerning these contracts are presented, highlighting the criteria used by courts to resolve such disputes. In conclusion, the article reaffirms the importance of a clear understanding of the concepts and norms governing exchange and barter in Brazilian civil law, both for legal professionals and individuals involved in commercial transactions. Furthermore, reflections on possible legislative updates and future challenges related to this topic are suggested